ArcGIS dashboard visualization on drug addiction trends in Malaysia (2015-2021) / Nur Afini Ismail and Sophia Nur Aisyah Jasfarizam - Ismail, Nur Afini; Jasfarizam, Sophia Nur Aisyah (Universiti Teknologi MARA (UiTM), 2024)
Drug addiction, particularly involving narcotics, poses a significant challenge to public health, social stability, and economic productivity in Malaysia. Despite various initiatives by community groups, NGOs, and government agencies, the prevalence of drug abuse continues to be a pressing concern. This study aims to analyze and visualize the trends and patterns of narcotics-related drug addiction in Malaysia from 2015 to 2021 using ArcGIS Dashboard. By integrating geospatial data with demographic and socioeconomic information, this project is able to identify high-risk areas, evaluate the effectiveness of intervention measures, and provide valuable insights for policymakers. This project employs a comprehensive approach to uncover correlations between drug addiction rates and socio-economic factors, facilitating a deeper understanding of the crisis.